Ethanol extract of Abrus precatorius L. leaves diminishes inflammatory responses in nicotine-treated human gingival fibroblasts: an in vitro study - Kesumaningtias, Raden Roro Widorini; Kusuma, Indra; Suciati, Yulia; Sari, Wening (Universa Medicina, 2024)
BACKGROUNDNicotine induces oxidative stress in human gingival fibroblasts (HGF) and stimulates the production of cytokines that trigger inflammation. Abrus precatorius L. (AP) leaves contain antioxidants with anti-inflammatory properties that can prevent the formation of free radicals and reduce tissue damage due to inflammation. This study aimed to determine the effect of ethanolic extract of AP leaves (EAP) on interleukin (IL-6) levels and cyclooxygenase-2 (COX-2) gene expression in gingival fibroblasts exposed to nicotine. METHODSCells were randomized into six treatment groups and clustered into the non-treatment control group (NTC), solvent control (SC), nicotine control (NC), and groups treated with nicotine and EAP at doses of 9.375 µg/mL, 18.75 µg/mL, and 37.5 µg/mL, respectively, for 24 hours. IL-6 levels were examined using the Elisa method, while COX-2 gene expression was assessed using PCR. Data were analyzed using Oneway ANOVA and the Kruskal Wallis test. RESULTSIL-6 levels and COX-2 expression were considerably higher in the nicotine control group. Conversely, the cell groups treated with nicotine and EAP had substantially decreased levels of both inflammatory markers IL-6 and COX-2 (p=0.029) across all EAP dose levels compared to the nicotine control group. The highest reduction in response was observed at the dose of 9.375 ìg/mL EAP. CONCLUSIONThese results highlight the potential of Abrus precatorius L. in relieving nicotine-induced inflammation in smokers. By suppressing the production of inflammatory mediators IL-6 and COX-2 in HGF, EAP presents a promising avenue for further in vitro research.